International Journal of Productivity and Performance Management. - Edgeman, Rick; Eskildsen, Jacob (International Journal of Productivity and Performance Management: Volume 64, Issue 3., 2015)
This ebook focusing on Continuously Relevant and Responsible Organizations via Creativity, Innovation and Sustainability is an outgrowth of the June 2014 Performance Management Association (PMA) Conference. PMA focuses on performance measurement and management and - certainly - enhanced performance across many domains that include productivity.